AHP 35: Review Essay: COMPARATIVE BORDERLANDS ACROSS DISCIPLINES AND ACROSS SOUTHEAST ASIA - William B., Noseworthy (Asian Highlands Perspectives, 2018)
Early in the colonial period, many studies examining upland Southeast Asia focused on ethnography and ecology as a means for the colonial state to better understand the region's geography. This process resulted in the construction of physical, social, and intellectual boundaries that sought to maintain control of the colonial enterprise. The natural borderlands of the region defied such easy definition – the highlands, the plains at the edges of deltas, and heavily forested regions – became a fascination of colonial study. In the climate of pending Association of Southeast Asian Nations (ASEAN) integration, which promises to begin the process of loosening restrictions for border crossing between Southeast Asian states by area residents, the study of borderlands has risen again. Because many of these border areas have pockets of highlands culture, continued study of the uplands is particularly relevant to deepening an understanding of the region. This review of several books on the Southeast Asian uplands explores historical and cultural strategies of individuals, particularly in Laos, Thailand, Vietnam, the Dayak community on the island of Borneo, and the Cham community in Vietnam and Cambodia, as well as some of the challenges that they face regarding 'the borderlands'. Putting these studies in conversation can help develop an interdisciplinary dialogue between scholars in Anthropology, Political Science, Linguistics, Ethnomusicology, and History, allowing for a more integrated international perspective.